Identification of a Rare EGFR T790I Mutation in Lung Adenocarcinoma Sensitive to Osimertinib - Wang, Yu; Liu, Songtao; Feng, Alei; Luo, Huan; Hu, Jinwei; Wang, Kai; Dong, Wei (Frontiers in Oncology, 2021)
EGFR-sensitive mutations are extremely important for targeted treatment strategies in lung cancer. Osimertinib can effectively inhibit the activity of EGFR-sensitive mutations, including the T790M mutation. However, the efficiency of osimertinib for rare mutation types of T790 is unclear. Here, we report the case of a Chinese patient with lung adenocarcinoma (LADC) harboring a T790I mutation who achieved significant benefits from osimertinib treatment.